Customer Insight Towards Start-Up Business OF the Early Three Months Period with SWOT and Marketing Mix of 4PS Tools: A Case Study OF Pippi Petite Company - Sangkaningrat, Fitriasti; Iskandar, Budi Permadi (Journal of Business and Management, 2015)
Abstract -PIPPI PETITE is one of start-up business in F&B sector which sells panna cotta (dessert) that was established in 2014. To keep sustainable with its competitor, PIPPI PETITE needs to develop its business. PIPPI PETITE has to be able to perceive what the customer wants and also the problems being faced by customer regarding PIPPI PETITE, both are needed to boost the company performance and eventually to reach zero complaints from PIPPI PETITE customer.This research is also formed to know what kind of program development that suits PIPPI PETITE. To reach the conclusion of this research, SWOT (Strength, Weakness, Opportunity and Threat) of PIPPI PETITE is implemented based on the customer insight. Customer insight are being used to identify what the they want and what they thought as a problem of PIPPI PETITE in order to increase the company performance. By giving appropriate solution to the problems that were being faced by PIPPI PETITE based on the customer insight, hopefully customer can feel satisfied towards the product and service that were being provided by PIPPI PETITE so that PIPPI PETITE could develop its business in a better way. This customer insight research resulted in operational problem. PIPPI PETITE was considered unable to reach the coverage area as promised. This was caused by the limited service capacity in the delivery service. Aside of that, customer also felt that the product availability of PIPPI PETITE is not yet stable so there comes complains from product availability. Product availability was caused by the limited production capability of the current kitchen owned by PIPPI PETITE. Based on the analysis conducted in both operational problems, can be concluded that PIPPI PETITE needs to add distribution channel (consignment) in area that is considered unreachable currently by the delivery service. Another solution for the operational management is to maximize the kitchen function and the product storaging so that the number of production reaches the customerâ€™s desire.Â Keyword: Marketing Research, Consumer Insight, Business Development